An Answer Ranking Method in Medical Social Networks - Monteiro, Flávio; Santos, Tomaz A. M. R. dos; Bulcão-Neto, Renato de Freitas; Macedo, Alessandra Alaniz (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2018: Proceedings of the 24th Brazilian Symposium on Multimedia and the Web, 2018)
Patient-oriented medical social networks aim to help their users, with different levels of knowledge, by providing information and support on specific medical and health issues. As one of such pioneering networks, the MedHelp includes forums which allow interaction between users seeking health and medical information with other users who know or live in the context of the information, so they can share their experiences. However, there is no explicit control over what is being answered by users. Therefore, filtering and sorting the answers are fundamental tasks. This work presents PERank as a method and a tool which aim to order answers to questions on forums of medical social networks. By manipulating documents about Type 1 Diabetes disease, experimentation results demonstrate the feasibility of PERank for a low number of best-ranked answers being analyzed.